L’HÉTÉRO-REFORMULATION OU LA NÉGOCIATION DU SENS. INTERACTION VERBALE ET ARGUMENTATION DANS UN DÉBAT TÉLÉVISÉ SUR L’IDENTITÉ ET L’INTÉGRATION - Houda LANDOLSI (Studia Universitatis Babeș-Bolyai. Philosophia)
Hetero-reformulation as a negotiation of meaning strategy. Verbal interaction and argumentation in a televised debate on identity and integration issues. This paper approaches the question of interaction through the phenomenon of reformulation, or more specifically hetero-reformulation, in a televised debate involving issues of identity and integration. The analysis will show that in a reformulation, semantic equivalence between the source utterance and the reformulated utterance does not necessarily imply argumentative co-orientation; and that the paraphrastic reformulation may also indicate a lack of commitment to the utterance. Reformulation enables speakers to negotiate not only the content of the utterances and the direction the debate will take, but also the types of interactions within which they unfold.